RANCANG BANGUN APLIKASI PENCARIAN SALES DAN PENDAFTARAN ONLINE WIFI INDIHOME BERBASIS ANDROID - Tri Indriyani; Jenie Sundari (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
Indonesia Digital Home or Indihome is one of the second largest subsidiaries after Telkomsel from PT Telkom Indonesia Tbk, which is engaged in providing telecommunications and network services. As we know that this year the whole world is experiencing a case of the corona virus (Covid-19) which makes the whole community required to carry out almost 80% of activities that are done from home. The purpose of this application is to know the existence of sales locations to make it easier for prospective customers who want to register wifi indihome with android. The method used for this application is geographic information services with analysis (surveys, interviews and literature studies) and design, while for the database using MYSQL. The results of the application design can be used for prospective customers, sales and survey teams.